Potassium Cyanate as an Inhibitor of the Sickling of Erythrocytes In Vitro - Cerami, Anthony (1971)
The recent use of urea as a treatment for the crisis phase of sickle-cell anemia has prompted us to investigate the possibility that cyanate, which is in equilibrium with urea in solution, might itself prevent the sickling of erythrocytes. We have found that in contrast to the high concentration of urea (1 M) needed to prevent reversibly the in vitro sickling of 80% of the cells, potassium cyanate (0.01-0.10 M) irreversibly inhibits sickling to the same extent. The prevention of sickling is a function of the amount of [(14)C]cyanate incorporated into acidprecipitable protein (0.1-1.0 mol of cyanate per mol of hemoglobin). Most of the radioactivity is accounted for by carbamylation of the NH(2)-terminal valine residues of hemoglobin; there is no detectable carbamylation of the lysine or cysteine residues. The reactive species, HN=C=O (isocyanic acid), may be an analog of O=C=O since both compounds bind to the same valine residues of hemoglobin. Deoxygenated sickled cells also incorporate [(14)C]-cyanate, but the sickling is not reversed. Oxygenation results in normal morphology in 75% of these cells. Upon subsequent deoxygenation, these cells remain normal. Potassium cyanate (5 mM) was also found to be an effective inhibitor of the gelling of deoxyhemoglobin S.